Nitrile N-Oxides and Nitrile Imines as New Fuels for the Discovery of Novel Isocyanide-Based Multicomponent Reactions - Giustiniano, Mariateresa; Novellino, Ettore; Tron, Gian Cesare (Synthesis, 2016)
With this short review we would like to describe our work on isocyanide-mediated multicomponent reactions using the 1,3-dipolar species nitrile N-oxides and nitrile imines as electrophilic inputs. Our goal is to show the potentiality of these transformations, elucidate the mechanisms of the reactions, demonstrate the versatility, and highlight the potentiality of this chemistry.1 Introduction2 (Z)-Chloroximes as Electrophilic Partners for Isocyanides2.1 Precedents for the Reaction Between Nitrile N-Oxides and Isocyanides2.2 Reaction between (Z)-Chloroximes, Isocyanides, and Carboxylic Acids (or Amines)2.3 The Use of Other Nucleophiles as the Third Partner2.4 General Mechanism3 Nitrile Imines as Electrophilic Partners for Isocyanides4 Conclusions and Future Outlook
Keywords: isocyanides; multicomponent reactions; Passerini reaction; nitrile N-oxides; cycloaddition reactions; chloroximes; nitrile imines